2015
DOI: 10.1063/1.4919810
|View full text |Cite
|
Sign up to set email alerts
|

Gadolinia nanofibers as a multimodal bioimaging and potential radiation therapy agent

Abstract: Continuous bead-free C-type cubic gadolinium oxide (Gd2O3) nanofibers 20-30 μm long and 40-100 nm in diameter were sintered by sol-gel calcination assisted electrospinning technique. Dipole-dipole interaction of neighboring Gd3+ ions in nanofibers with large length-to-diameter aspect ratio results in some kind of superparamagnetic behavior: fibers are magnetized twice stronger than Gd2O3 powder. Being compared with commercial Gd-DTPA/Magnevist®, Gd2O3 diethyleneglycol-coated (Gd2O3-DEG) fibers show high 1/T1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…A Summary of nanomaterials for enhancing EBRT. Element Materials References Gold Au nanoparticles/nanorods/nanoshells [31][32][33][34][35][36][37][38][39] Au loaded polymeric nanocapsules [40][41][42][43] Au nanomolecules [40,44,45] Active targeting Au nanoparticles [44,[46][47][48][49][50] Rare earth element Gadolinium oxide; Gd doped carbon dots; Gd doped calcium phosphate [51][52][53][54] Upconversion nanoparticles (e.g.NaYbF 4 [82][83][84] Pt nanoparticles [85,86] Ag nanoparticles; Fe 3 O 4/ Ag nanocomposite [87][88][89][90][91] Non high-Z elements Iron oxide nanoparticles [92][93][94] TiO 2 nanoparticles/nanotubes [95,96] Si nanoparticles [97,98] www.advmat.de www.advancedsciencenews.com (1.9 nm) -loaded polymeric micelles that exhibited longer blood circulation and 6-fold increase in tumor uptake, compared to that of ultrasmall Au nanoparticles...…”
Section: Doi: 101002/adma201700996mentioning
confidence: 99%
“…A Summary of nanomaterials for enhancing EBRT. Element Materials References Gold Au nanoparticles/nanorods/nanoshells [31][32][33][34][35][36][37][38][39] Au loaded polymeric nanocapsules [40][41][42][43] Au nanomolecules [40,44,45] Active targeting Au nanoparticles [44,[46][47][48][49][50] Rare earth element Gadolinium oxide; Gd doped carbon dots; Gd doped calcium phosphate [51][52][53][54] Upconversion nanoparticles (e.g.NaYbF 4 [82][83][84] Pt nanoparticles [85,86] Ag nanoparticles; Fe 3 O 4/ Ag nanocomposite [87][88][89][90][91] Non high-Z elements Iron oxide nanoparticles [92][93][94] TiO 2 nanoparticles/nanotubes [95,96] Si nanoparticles [97,98] www.advmat.de www.advancedsciencenews.com (1.9 nm) -loaded polymeric micelles that exhibited longer blood circulation and 6-fold increase in tumor uptake, compared to that of ultrasmall Au nanoparticles...…”
Section: Doi: 101002/adma201700996mentioning
confidence: 99%
“…The additional peak at 369 cm –1 appearing in the GDC-30 is the signature peak of the Gd 2 O 3 structure . In addition, a peak at 440 cm –1 also confirmed the presence of Gd 2 O 3 in the GDC-30 sample. This indicates that a second phase has formed in the GDC-30 sample.…”
Section: Resultsmentioning
confidence: 79%
“…2c) performed using the standard software option of the spectrometer showed peaks with a Gaussian distribution located at 1273, 1462, 1600, 1845, and 2111 cm -1 . Comparing literature data, it was found that the modes at 1273, 1845, and 2111 cm -1 are associated with Raman vibrations of the Gd-O structure [13][14][15]. Whereas, the peaks at 1462 and 1600 cm -1 refer to vibrations of Si scattering of the third order due to optical phonons (TO) [14][15][16] and vibrations of interstitial oxygen (O 2 ), respectively [15][16][17].…”
Section: Eejp 3 (2023)mentioning
confidence: 87%